THE EFFECT OF LEARNING HABITS, LEARNING DISCIPLINE, PARENTAL ATTENTION, AND FAMILY ENVIRONMENT ON THE LEARNING ACHIEVEMENT OF 10TH GRADE STUDENTS THROUGH LEARNING MOTIVATION AS AN INTERVENING VARIABLE INTERVENING VARIABLE IN THE SUBJECT OF ECONOMICS AT SM - Hidayat, Deny; Vivina Eprillison; Dina Amaluis (Global Action and Education for Society, 2025)
This study aims to analyze: 1) the effect of study habits on learning motivation, 2) the effect of study discipline on learning motivation, 3) the effect of parental attention on learning motivation, 4) the effect of family environment on learning motivation, 5) the influence of learning habits on learning achievement, 6) the influence of learning discipline on learning achievement, 7) the influence of parental attention on learning achievement, 8) the influence of family environment on learning achievement, 9) the influence of learning motivation on learning achievement. This research is associative in nature. The population in this study was 332 students in phase E at SMA Negeri 1 Sitiung in the 2024/2025 academic year. The sample consisted of 149 people using proportional random sampling. The research instrument used in this study is a closed-ended questionnaire, with path analysis and hypothesis testing using the t-test. The results of this study indicate that: 1) there is an influence of study habits on learning motivation, as shown by a path coefficient of 0.182 with a t-value of 3.164 > t-table 1.65514, 2) there is no influence of study discipline on learning motivation, as indicated by a path coefficient of 0.171 with a t-value of 1.576 < t-table 1.65514, 3) there is an influence of parental attention on learning motivation, as indicated by a path coefficient of 0.233 with a t-value of 2. 754 > t-table 1.65514, 4) There is an effect of family environment on learning motivation, as indicated by a path coefficient of 0.367 with a t-value of 3.126 > t-table 1.65514, 5) There is a negative effect of learning habits on academic achievement, as indicated by a path coefficient of -0.470 with a t-value of -4.836 < t-table 1.65514, 6) there is no influence of learning discipline on academic achievement, as indicated by a path coefficient of -0.252 with a t-value of -1.404 < t-table 1.65514, 7) There is an influence of parental attention on academic achievement, as indicated by a path coefficient of 0.533 with a t-value of 3.885 > t-table 1.65514, 8) There is an influence of family environment on academic achievement, as indicated by a path coefficient of 0.724 with a t-value of 3.640 > t-table 1.65514, 9) There is a negative influence of learning motivation on academic achievement, as indicated by a path coefficient of -0.661 with a t-value of -4.845 < t-table 1.65514.